(untitled) (LACCEI, 2024)
Currently, SMEs are influenced by the technological advances that the business world is evolving, and the constant changes in customer preferences, which is why digital marketing and customer-oriented business management will be discussed. The objective of this research was to determine how digital marketing influences business management oriented to customer value in SMEs, San Juan de Lurigancho, Lima 2021. The type of research is basic, with a quantitative approach, at an explanatory level and Its design is non-experimental with a cross section. The population was made up of all the clients of the SMEs in the San Juan de Lurigancho district that make purchases online, with a nonprobabilistic sample for convenience, made up of 180 clients. The applied technique was the survey and the instrument used by a questionnaire, validated by experts and applicable result and For reliability, Cronbach’s Alpha coefficient was used, demonstrating high statistical reliability. Thus, it was determined that digital marketing significantly influences business management oriented towards customer value in SMEs, demonstrated by regression analysis with a global significance level of ANOVA 0.05 and contrasted with the R-Squared statistic =0.582. In other words, digital marketing explains customer-oriented business management in that magnitude.